LIFE EXPERIENCES OF PULMONARY TUBERCULOSIS PATIENTS AFFECTED BY DELAYS IN TREATMENT, IN THAILAND - Chaychoowong, Kampanart (LIFE: International Journal of Health and Life-Sciences, 2019)
A qualitative research aimed to describe life experiences of pulmonary tuberculosis (TB) patients affected by delays in treatment among 25 pulmonary TB patients in Nakhon Ratchasima, Thailand from October to December 2018. The data were collected by in-depth interviews, analyzed by the content analysis, and managed with the NVivo version 12. The findings found there were two major consequences: patient-related and community-related consequences. For the patient-related consequences, patients claimed that they had more severe symptoms before getting treatment. It affected their daily-life including work that led them to stop working or leave their job. The result of having a longer duration of delays in treatment increased the severity of the disease which may result in death. For the community-related consequences, patients had opinions that they could spread TB to other people. However, some patients felt that they could not spread TB germs because the TB screening test results were not found in the infection. These findings can be used for improving the TB controlling strategies by exchanging knowledge and experience of these TB patients which may help to reduce the severity of the disease, mortality rate, and transmission rate in the community.